Comprehensive 3E (Energy, exergy, and emissions) analysis and sustainability assessment of SiO₂-enhanced water-diesel emulsified fuel - Rahul Goyal; Parth Deepak Kusalkar; A.F. Yusop (Results in Engineering, 2025)
Although diesel engines are required for transportation and energy generation, they also significantly worsen environmental pollution. Researchers have investigated alternative fuel options to reduce these pollutants. The current study examines the effectiveness of water diesel emulsified fuel (WDEF) combined with SiO₂ nanoparticles at different dose levels at increments of 25 ppm, ranging from 25 to 100 ppm. The study focuses on an integrated analysis of energy and exergy metrics, emission behaviour, and overall sustainability as indicated by the Sustainability Index (SI). A diesel engine was tested for this investigation with a full load of 12 kg and a constant speed of 1500 RPM to ensure experimental consistency. The D94W5S1-Si50 blend demonstrates the highest useful work (32.7 %) and the lowest exergy destruction or thermal losses (7.7 %). At a 50-ppm dosage of SiO₂ nanoparticles in WDEF, the work exergy output reaches its peak (39.72 %), while exergy destruction is minimized (24.98 %). Among all tested fuel blends, D94W5S1-Si50 achieves the highest energy and exergy efficiencies at 32.68 % and 39.69 %, respectively, under full engine load conditions. Nanoparticle-based WDEF improves sustainability and combustion, with Si50 attaining the highest sustainability index (1.658), though further increases in nanoparticle concentration lead to energy losses due to poor atomization and increased viscosity. Therefore, this study recognizes D94W5S1-Si50 as the improved fuel blend, offering more engine performance. This arrangement not only maximizes energy and exergy efficiencies but also suggestively decreases CO and NOx emission features, making it the most desirable choice among the different tested blends.